2021
DOI: 10.1371/journal.pone.0252985
|View full text |Cite
|
Sign up to set email alerts
|

Response of essential oil hemp (Cannabis sativa L.) growth, biomass, and cannabinoid profiles to varying fertigation rates

Abstract: Five essential oil hemp (Cannabis sativa L.) cultivars (Cherry Blossom, Cherry Blossom (Tuan), Berry Blossom, Cherry Wine, and Cherry Blossom × Trump) were treated with six fertigation treatments to quantify the effects of synthetic fertilizer rates and irrigation electrical conductivity on plant growth, biomass accumulation, and cannabinoid profiles. Irrigation water was injected with a commercial 20-20-20 fertilizer at rates of 0, 50, 150, 300, 450, and 600 ppm nitrogen equating to 0.33 (control), 0.54, 0.96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
(51 reference statements)
8
21
1
Order By: Relevance
“…Decarboxylated cannabinoids such as CBD and CBN (cannabinol) concentration decrease at extremely high and low N concentrations (Saloner & Bernstein, 2020). Comparable results are reported in another study where CBD and CBG (cannabigerol) yields were meager at 0 mg L −1 N. A subsequent reduction occurred when the N concentration was increased above 50 mg L −1 (Anderson et al., 2021). In a field study, it has been reported that bud biomass and CBD yield per plant increase quadratically with the increase in fertilizer N, with the optimum N range being 140–190 kg ha −1 (Atoloye et al., 2022).…”
Section: Nitrogen Management and Fiber Seed And Flower Productionsupporting
confidence: 68%
See 2 more Smart Citations
“…Decarboxylated cannabinoids such as CBD and CBN (cannabinol) concentration decrease at extremely high and low N concentrations (Saloner & Bernstein, 2020). Comparable results are reported in another study where CBD and CBG (cannabigerol) yields were meager at 0 mg L −1 N. A subsequent reduction occurred when the N concentration was increased above 50 mg L −1 (Anderson et al., 2021). In a field study, it has been reported that bud biomass and CBD yield per plant increase quadratically with the increase in fertilizer N, with the optimum N range being 140–190 kg ha −1 (Atoloye et al., 2022).…”
Section: Nitrogen Management and Fiber Seed And Flower Productionsupporting
confidence: 68%
“…Hemp is an annual, windpollinated plant with a height of 1-5 m, depending on the genotype (Bouloc et al, 2013). Nitrogen application increases plant height significantly in flower, seed, and fiber hemp under field and greenhouse conditions and has been reported in several studies (Anderson et al, 2021;Papastylianou et al, 2018;Vera et al, 2010;Yang et al, 2021;Zhu et al, 2022). N application also increases stem diameter (Yang et al, 2021;Zhu et al, 2022).…”
Section: Morphologymentioning
confidence: 96%
See 1 more Smart Citation
“…Environmental factors, such as soil temperature, air humidity, and precipitation, affected total CBD and total THC concentration in flowers of IH in different ways under open field conditions (Sikora et al, 2011). In addition, studies in controlled environments reported that total CBD and total THC concentration in cannabis plants responded to different fertilization treatments (Anderson et al, 2021;Bócsa et al, 1997;Caplan et al, 2017;Coffman & Gentner, 1975, 1977. Taken together, these results provide a strong incentive to elucidate genetic stability of cannabinoid content in high-CBD hemp cultivars across different field-scale production systems.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there has been significant interest in cultivating CBD‐dominant hemp cultivars for their medicinal uses. Many studies are being conducted to identify suitable cultivars and cultural practices for CBD‐dominant industrial hemp cultivation in different agroclimatic regions including Florida (Anderson et al., 2021; Yang et al., 2020; Zhang et al., 2021). However, in several areas such as Florida, high CBD yielding cultivars are also accompanied with high THC concentrations (Yang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%